Distribution pattern of anthropogenic marine debris along the gastrointestinal tract of green turtles (Chelonia mydas) as implications for rehabilitation. Issue 1 (15th June 2017) - Colferai, André S.; Silva-Filho, Rodolfo Pinho; Martins, Aryse Moreira; Bugoni, Leandro
Abstract: Pollution from anthropogenic marine debris (AMD) is currently the most widely distributed and lasting anthropic impact in the marine environment, affecting hundreds of species, including all sea turtles. In this study, the patterns of AMD distribution along the gastrointestinal tract (GT) and their relationship with obstructions and faecalomas in 62 green turtles ( Chelonia mydas ) that died during rehabilitation in southern Brazil were determined. The GT was split in seven sections, corresponding to the natural organs and intestinal areas morphologically and physiologically distinct. Mean mass (4.24 g) and area (146.74 cm 2 ) of AMD in the stomach were higher than in other sections. The anterior portion of the rectum had the highest number of obstructions, followed by the stomach. AMD was associated with the obstructions, with positive correlation between faecalomas and AMD masses. Organs and subdivisions showed marked differences in susceptibility to obstructions caused by AMD, which deserves attention in clinical interventions. Graphical abstract: Highlights: Plastic is the anthropic debris most commonly ingested by juvenile sea turtles. The most frequently found debris in the gastrointestinal tract was light in colour. Different regions of the gastrointestinal tract have different susceptibilities to debris retention. The amount of debris is associated with the size of the faecalomas and debilitation.